CRISPR/Cas9‐mediated MSTN disruption accelerates the growth of Chinese Bama pigs. Issue 10 (14th August 2020) - Zhu, Xiang‐Xing; Zhan, Qun‐Mei; Wei, Yan‐Yan; Yan, Ai‐Fen; Feng, Juan; Liu, Lian; Lu, Sheng‐Sheng; Tang, Dong‐Sheng
Abstract: CRISPR/Cas9‐mediated genome editing technology is a simple and highly efficient and specific genome modification approach with wide applications in the animal industry. CRISPR/Cas9‐mediated genome editing combined with somatic cell nuclear transfer rapidly constructs gene‐edited somatic cell‐cloned pigs for the genetic improvement of traits or simulation of human diseases. Chinese Bama pigs are an excellent indigenous minipig breed from Bama County of China. Research on genome editing of Chinese Bama pigs is of great significance in protecting its genetic resource, improving genetic traits and in creating disease models. This study aimed to address the disadvantages of slow growth and low percentage of lean meat in Chinese Bama pigs and to knock out the myostatin gene ( MSTN ) by genome editing to promote growth and increase lean meat production. We first used CRISPR/Cas9‐mediated genome editing to conduct biallelic knockout of the MSTN, followed by somatic cell nuclear transfer to successfully generate MSTN biallelic knockout Chinese Bama pigs, which was confirmed to have significantly faster growth rate and showed myofibre hyperplasia when they reached sexual maturity. This study lays the foundation for the rapid improvement of production traits of Chinese Bama pigs and the generation of gene‐edited disease models in this breed.